Topographic analysis of macular choriocapillaris flow deficits in diabetic retinopathy using swept–source optical coherence tomography angiography - Isaac Gendelman; A. Yasin Alibhai; Eric M. Moult; Emily S. Levine; Phillip X. Braun; Nihaal Mehta; Yi Zhao; Akihiro Ishibazawa; Osama A. Sorour; Caroline R. Baumal; Andre J. Witkin; Elias Reichel; et al. (International Journal of Retina and Vitreous, 2020)
Abstract Background The purpose of this study was to investigate the association between diabetic retinopathy (DR) severity and macular choriocapillaris (CC) flow deficit percentage (FD %) in different macular regions using swept-source optical coherence tomography angiography (SS-OCTA). Methods Diabetic patients with SS-OCTA images were graded by severity and retrospectively assessed. CC FD % was calculated in four different regions of the OCTA image: inner, middle, outer, and full-field region. The generalized estimating equations (GEE) approach for clustered eye data was used to determine effect size and significance of age and disease severity on FD % for each region. Results 160 eyes from 90 total diabetic patients met inclusion criteria. Out of 90 patients, 33 had no DR, 17 had mild nonproliferative DR (NPDR), 8 had moderate NPDR, 10 had severe NPDR and 22 had proliferative DR. Age and DR severity had a significant positive association with FD % for each region studied with a greater effect in the two centermost regions. The increase in flow deficit percentage per year of age by region was: inner 0.12 (p < 0.001), middle 0.09 (p < 0.001), outer 0.05 (p < 0.001, full-field 0.06 (p < 0.001). The increase in flow deficit percentage per increase in diabetic retinopathy severity stage by region was: inner 0.65 (p < 0.0087), middle 0.56 (p < 0.0012), outer 0.33 (p < 0.045), full-field 0.36 (p < 0.018). Conclusions Topographic analysis of the CC FD % in diabetic eyes suggests that CC flow impairment corresponds to DR severity, with all studied regions of the CC significantly affected. There was greater regional impairment due to age and disease severity in the inner and middle regions.